Continuous Estimates of Glacier Mass Balance in High Mountain Asia Based on ICESat‐1,2 and GRACE/GRACE Follow‐On Data - Qiuyu Wang; Shuang Yi; Wenke Sun (Geophysical Research Letters)
Abstract Glacier melt in High Mountain Asia (HMA) is an indicator of climate change and has a major impact on the regional hydrology and freshwater supply. We determined the recent status of HMA glaciers based on the first analysis of Ice, Cloud, and Land Elevation Satellite‐2 (ICESat‐2) data. We used the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow‐On (FO) data to complement ICESat‐1,2 data and validate them independently. We find a good agreement between ICESat‐1,2 and GRACE/GRACE‐FO data, which demonstrates the high reliability of results. Based on our results, the continuous glacier mass change from 2003 to 2019 is −28 ± 6 Gt yr−1, which is more negative than stereo imagery‐based studies. The regional variability of the glaciers ranges from −1.07 ± 0.10 m yr−1 in southeastern Nyaingentanglha to +0.16 ± 0.10 m yr−1 in West Kunlun. ICESat‐2 data enable new insight into the continuous measurement of HMA glacier elevation change.